KEPERAWATAN KELUARGA DALAM PROGRAM INDONESIA SEHAT (PIS) DI KABUPATEN ENDE TAHUN 2018 - Aris Wawomeo (Poltekkes Kemenkes Kupang, 2022)
The implementation of the Healthy Indonesia Program (PIS) with a family approach at the public health center (Puskesmas) level is carried out through activities to collect health data on all family members and implement the Puskesmas Information and Reporting System. The purpose of this studyidentified the Implementation of Family Nursing in the Healthy Indonesia Program (PIS) in Ende Regency in 2018. This study is a descriptive study, the research sample is 50 nurses and 50 documents/family status. The sample criteria include implementing nurses with civil servant status with a service period of 2 years or more. Sampling by means of stratified clusters or stratified clusters. Data analysis was carried out through a statistical chi square test with a meaningfulness level of 95%. The chi square statistical test is used to test the difference in proportion or percentage between several groups of data. The results of research on influencing factors showed that 60% stated that funds were lacking for the implementation of the family approach of the PIS, 30% of good funds, and 10% were sufficient. Based on the factor of understanding of the family approach in PIS, 68% factor is good, 24% is sufficient, and 8% is less. Socialization factors, 40% less, 30% sufficient, and 30% good. Superior feedback aspect, 70% good category, 20% enough, and 10% less. The results of the study can be that there is less financial support for the implementation of the family approach, lack of understanding, socialization, and superior feedback did not have a significant influence (values p = 0.735, p = 0.854, p = 0.894, and p = 0.882) on the implementation of the familyapproach in PIS at puskesmas in the Ende Regency Region in 2018. It is recommended to increase theimplementation of home visits, increase PIS socialization activities, and optimize family empowerment to strengthen promotive and preventive health efforts